2016
DOI: 10.1002/ptr.5692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Capsicoside G‐rich Fraction from Pepper (Capsicum annuum L.) Seeds on High‐fat Diet‐induced Obesity in Mice

Abstract: Obesity is one of the most common metabolic syndromes and is a major threat to human health worldwide. Given the size of this problem, there is growing interest in natural agents that may decrease obesity. In this study, we investigated the anti-obesity effect of a capsicoside G-rich fraction (CRF; 13.35% capsicoside G) isolated from pepper seeds in diet-induced obese mice. C57BL/6J mice were fed either a normal diet or a high-fat diet (HFD), with or without CRF (HFD + CRF; 10 and 100 mg/kg body weight). The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
4
14
2
2
Order By: Relevance
“…ESEE also suppressed weight increases of eWAT, and of organs including the liver, spleen and kidneys versus HFd-fed mice. These findings are in accordance with those of a previous study, in which a capsicoside G-rich fraction from pepper exhibited anti-obesity effects in HFd-induced obese mice (23).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ESEE also suppressed weight increases of eWAT, and of organs including the liver, spleen and kidneys versus HFd-fed mice. These findings are in accordance with those of a previous study, in which a capsicoside G-rich fraction from pepper exhibited anti-obesity effects in HFd-induced obese mice (23).…”
Section: Discussionsupporting
confidence: 93%
“…The induction of obesity in animals via HFd supplementation is the most popular means of mimicking obesity in human, and a number of studies have been conducted using HFd-induced obese mouse models, in which HFd supplementation increases abdominal fat and body weights (22). Previous studies have reported crude plant extracts and natural compounds isolated from them induce weight loss and prevent diet-induced obesity (17,23). Although, E. supina is known to have potent anti-oxidant, anti-aging and anti-cancer effects, its effects on obesity have not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…During the feeding period, food intake was higher in the SD than in the HFD groups. Similar food behavior was demonstrated previously [19]. This result can be attributed to high caloric density of HFD in comparison to SD.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed in previous studies that HFD compared to SD group, exhibited markedly higher body weight and capsinoids could prevent huge body weight gain [19]. These results were controversial in our study, because HFD and HFDC groups presented less weight gain when compared to SD and SDC respectively.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation